2017
DOI: 10.4236/ojst.2017.712049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malocclusions and Normative Orthodontic Treatment Need Using IOTN Index for Patients in Yalgado Ouédraogo Teaching Hospital

Abstract: Introduction: The assessment of health care needs must be reproducible, independent of the operator, hence the use of indexes like the Index of Orthodontic Treatment Need (IOTN). The aim of this study was to assess both, the prevalence of malocclusions among patients received in the Dental Surgery Unitat Yalgado Ouédraogo Teaching Hospital and their care needs according to IOTN index. Materials and Methods: It is a prospective, cross-cutting diagnostic study of malocclusions at Yalgado Ouédraogo Teaching Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The level of need for treatment was assessed using the dental health component (DHC) in the index of orthodontic treatment need (IOTN). The results of this study was also supported by previous research conducted by Ouedraogo et al 22 , which demonstrated that 91.4% of adolescent patients visiting orthodontic clinics required orthodontic treatment. Also, another study by Nobile et al 23 showed that 59.5% of the respondents, children and adolescents, belong to the grade 4 and 5.23 level of treatment needs.…”
Section: Discussionsupporting
confidence: 90%
“…The level of need for treatment was assessed using the dental health component (DHC) in the index of orthodontic treatment need (IOTN). The results of this study was also supported by previous research conducted by Ouedraogo et al 22 , which demonstrated that 91.4% of adolescent patients visiting orthodontic clinics required orthodontic treatment. Also, another study by Nobile et al 23 showed that 59.5% of the respondents, children and adolescents, belong to the grade 4 and 5.23 level of treatment needs.…”
Section: Discussionsupporting
confidence: 90%